2021
DOI: 10.1039/d1nj03440e
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the chemiexcitation of dioxetanones by replacing the peroxide bond with S–S, N–N and C–C bonds

Abstract: Dioxetanone is one of the prototypical cyclic peroxide intermediates in several chemiluminescent and bioluminescent systems, in which thermolysis reactions allow for efficient singlet chemiexcitation. While the chemiexcitation mechanism of dioxetanone...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
40
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(52 citation statements)
references
References 57 publications
12
40
0
Order By: Relevance
“…However, theoretical and experimental studies indicated the possible involvement of neutral dioxetanones in efficient chemiexcitation, instead of anionic species [26][27][28][29][30]. More specifically, theoretical calculations made by our team revealed seemingly more beneficial chemiexcitation profiles [26,29,30]. In turn, Hirano et al [27] performed an experimental and theoretical study of the chemiluminescence of Cypridina analogues and stated that the reaction mechanism of the chemiluminescence of neutral species should explain the highly efficient chemiexcitation of Cypridina bioluminescence.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, theoretical and experimental studies indicated the possible involvement of neutral dioxetanones in efficient chemiexcitation, instead of anionic species [26][27][28][29][30]. More specifically, theoretical calculations made by our team revealed seemingly more beneficial chemiexcitation profiles [26,29,30]. In turn, Hirano et al [27] performed an experimental and theoretical study of the chemiluminescence of Cypridina analogues and stated that the reaction mechanism of the chemiluminescence of neutral species should explain the highly efficient chemiexcitation of Cypridina bioluminescence.…”
Section: Introductionmentioning
confidence: 86%
“…From this resulted the Charge Transfer-Initiated Luminescence (CTIL) mechanism [24,25]. However, theoretical and experimental studies indicated the possible involvement of neutral dioxetanones in efficient chemiexcitation, instead of anionic species [26][27][28][29][30]. More specifically, theoretical calculations made by our team revealed seemingly more beneficial chemiexcitation profiles [26,29,30].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations